Cinema culture and audience rituals - Pušnik, Maruša (Anthropological notebooks, 2015)
Cinema played an important role in the creation of media culture and in the mediatisation processes in the societies of the 20th century. In this paper, I use the cultural-historical approach and Geertz's thick description method to analyse cinema-going practices and audiences' ritual uses of cinema in Slovenia. Around 180 interviews with cinemagoers helped me to collect their memories of cinema-going habits to find out how the mediatisation of society is intertwined with ritualised human action. In its early and in its golden years, cinema was closely connected with sociability and functioned as an important social and leisure space for the emerging mass audience. With the examples from the Slovenian society until the 1970s I illustrate how ritualisation had been an integral part of mediatisation processes when cinema started to cultivate and disseminate specific media dispositions through the ritual practices.
Keywords: film; kino; občinstvo; mediatizacija; medijska kultura; ritualizacija; Slovenia; Slovenija